INTERRELATEDNESS OF LEGAL VERSES IN SURAH AL-BAQARAH - Jamilah, Jamilah (De Jure: Jurnal Hukum dan Syari'ah, 2009)
This paper will examine the interrelatedness of the Quranic verses, and how every verse is put in a well logical arrangement. The approach used in this examination is what the Quranic science calls â€˜Ilm al-MunÃ¢sabah. This specific Quranic science aims to find the relation between one verse with the other which precedes and follows it. Different issues, styles, time and occasions of revelation in one chapter are not a hindrance to find the correlation between the verses of the same chapter. Due to its various legal contents, surah al-Baqarah will be the focus of the discussion.Artikel ini meneliti keterkaitan antar ayat al-Quran dan bagaimana setiap ayat diposisikan dalam urutan yang logis. Pendekatan yang digunakan dalam tulisan ini adalah apa yang dikenal sebagai ilm munasabah al-ayat. Ilmu al-Quran ini berupaya menemukan keterkaitan antara satu ayat dengan ayat sebelum dan sesudahnya. Ragam tema, gaya, waktu dan asbab al-nuzul dalam sebuah surat tidak menjadi hambatan untuk menemukan hubungan antarayat dalam surat yang sama. Karena kandungan ayat hukumnya yang beragam, surat al-Baqarah menjadi fokus kajian dalam artikel ini.